An Analysis of PBI UINSU Students’ Understanding of Imperative Sentences In English Syntax - Siregar , Hanny Sarah; Azmy , Nabila Putri; Putri, Suci Aisya; Ismahani, Siti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to analyze PBI UINSU students’ understanding of imperative sentences in English syntax. The research employed a quantitative descriptive method involving five students from the English Education Study Program at Universitas Islam Negeri Sumatera Utara. Data were collected through a Google Form questionnaire consisting of ten multiple-choice questions and one Likert-scale item focusing on the definition, structure, verb forms, subject omission, negative imperatives, politeness, and students’ self-confidence in using imperative sentences. The findings reveal that students demonstrate a strong understanding of the basic syntactic features of imperative sentences, including correct verb forms, implicit subjects, and negative constructions. However, minor difficulties were identified in recognizing polite imperative forms, indicating challenges in pragmatic aspects. In addition, although students reported feeling confident in using imperative sentences, the results suggest a gap between grammatical knowledge and pragmatic awareness. In conclusion, while PBI UINSU students possess solid foundational knowledge of imperative sentence structures, further instructional emphasis on pragmatic competence, particularly politeness strategies, is necessary.